Elaboração de um guia de orientação para celíacos - GOMES, Ana Luisa Bezerra Soares (2023)
Objective: To develop and validate a guidance guide for newly diagnosed celiac patients to assist in the adoption of a gluten-free lifestyle and diet. Methodology: This is a methodological study, or what is seen as a treatment for a guidance guide for celiac or celiac caregivers. The content presented in the guide was defined by surveying and defining the theoretical framework, Resources and Topics that should be started in the guide; Consultation by the target audience on the proposed topics and final structuring of the guide, with a selection of images and graphics. Results: The guide consisted of 14 topics, 16 images and a total of 25 pages. Thirty technicalscientific documents on celiac disease (articles and books) were consulted for writing and substantiation of topics, using images to reinforce textual information. On each page, simple training topics were used to facilitate public understanding. Conclusion: With a research of auxiliary educational materials in the context of celiac disease (CD), a creation of a tool that addresses this subject is fundamental for the dissemination of knowledge of the disease and health education. The guidance guide can be an important tool for health promotion through celiac disease education, with impressive information and tips on what celiac sufferers can achieve.